Nannobiostratigraphy and Paleoecology of Fat'ha Formation, Bashiqa Anticline, Northeastern Iraq - Al-Shareefi, Dr. Ibrahim; Al-Badrani, Omar; Kharofa, Luma (Iraqi Journal of Science, 2022)
Fifteen samples of limestone, marls and, clay from the Fat'ha Formation are obtained from the location of Bashiqa village, Bashiqa anticline, Northeastern Iraq. A detailed investigation is carried out, during which twenty-four species of calcareous nannofossils identified, twenty- one are descried from other regions while three are left under an open name because of lack of material or insufficient samples. Besides, seventeen species of Ostracoda fossils were picked and diagnosed, including two subspecies, belonging to ten genera, and four subgenera.The recorded calcareous nannofossil assemblages include two biozones which are from the lower to the upper part of the section: (1) Helicosphaera ampliaperta Interval Biozone (CNM6); (2) Discoaster signus Interval Biozone (CNM7). These biozones are correlated with other calcareous nannofossils biozones from both local and regional sections that lead to conclude the age of the Middle Miocene(Burdigalian to Laghian).The paleoenvironment of the Fat'ha Formation was determined through the use of the environmental evidence of the Ostracoda fossils, which indicated oscillating periods which vary from normal salinity to brackish and saline environments, with shallow lagoonal environment and sometimes deep lagoonal environment that do not exceed the margin of shelf zone.